Peri-urbanization, dynamics, and challenges in developing countries towards sustainable urban growth – Special Section Editorial - Barbosa, Vasco; Priya Rajendran, Lakshmi; Suárez Pradilla, Mónica Marcela (My University, 2022)
La periurbanización en países en desarrollo se ha intensificado debido al crecimiento poblacional, que ha llevado a una transformación física y social en las áreas periféricas de las ciudades. Este fenómeno, impulsado por la migración rural-urbana y la falta de planificación urbana adecuada, ha resultado en la expansión de asentamientos informales y en una creciente fragmentación urbana. La investigación destaca tres elementos clave: territorial, funcional y transicional, que ayudan a comprender estas dinámicas. Aunque la periurbanización contribuye a la economía, también impone altos costos sociales, ambientales y financieros. Se sugieren alternativas, como políticas de uso del suelo y estrategias de gestión sostenible, para abordar los desafíos que plantea este fenómeno en contextos como América Latina.

Peri-urbanization in developing countries has intensified due to population growth, leading to physical and social transformations in the peripheral areas of cities. This phenomenon, driven by rural-urban migration and inadequate urban planning, has resulted in the expansion of informal settlements and increasing urban fragmentation. The research highlights three key elements: territorial, functional, and transitional, that help to understand these dynamics. While peri-urbanization contributes to the economy, it also imposes significant social, environmental, and financial costs. Alternatives, such as land use policies and sustainable management strategies, are suggested to address the challenges posed by this phenomenon in contexts like Latin America.
Digital
Keywords: Desarrollo urbano; Cities and towns - Growth; Desarrollo sostenible; Sustainable development; Desarrollo urbano sostenible; Sustainable urban development